2001
DOI: 10.1897/1551-5028(2001)020<2883:eobvcc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bioassays Versus Contaminant Concentrations in Explaining the Macroinvertebrate Community Structure in the Rhine-Meuse Delta, the Netherlands

Abstract: It is often assumed that bioassays are better descriptors of sediment toxicity than toxicant concentrations and that ecological factors are more important than toxicants in structuring macroinvertebrate communities. In the period 1992 to 1995, data were collected in the enclosed Rhine-Meuse delta, The Netherlands, on macroinvertebrates, sediment toxicity, sediment contaminant concentrations, and ecological factors. The effect of various groups of pollutants (polycyclic aromatic hydrocarbons, trace metals, oil,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
0
18
1
1
Order By: Relevance
“…Percentages of explained variation by environmental and pollution variables are in the same range as found in other studies. In the Dutch Rhine-Meuse Delta and Dutch river branches, 45 to 72% of the variation in species composition could be explained by ecological and contaminant variables together [14].…”
Section: Quantifying Trace Metal Effects On Community Structurementioning
confidence: 98%
“…Percentages of explained variation by environmental and pollution variables are in the same range as found in other studies. In the Dutch Rhine-Meuse Delta and Dutch river branches, 45 to 72% of the variation in species composition could be explained by ecological and contaminant variables together [14].…”
Section: Quantifying Trace Metal Effects On Community Structurementioning
confidence: 98%
“…Prior work also indicated that habitat was a main driver of benthic communities in the Massena AOC (USFWS, 1979) and noted the relationship between habitat alteration and macroinvertebrate populations in the St. Lawrence River (Patch and Busch, 1986). Other investigations have found that habitat comparability is a critical requirement for assessing sediment-dwelling macroinvertebrate communities (Bond et al, 2014;Breneman et al, 2000;Cummins and Lauff, 1969;Panis et al, 1995;Peeters et al, 2001;Simpson et al, 1986;Smit et al, 1995). Reinhold-Dudok van Heel and den Besten (1999) used a similar substrate-classification approach (grouped sites by grain size and organic matter) to control for sediment heterogeneity while evaluating the impacts of contamination on macroinvertebrate communities.…”
Section: Discussionmentioning
confidence: 99%
“…Historical data collected by the NYSDEC Stream Biomonitoring Unit and others, however, indicate that benthic community structure was not necessarily correlated with the presence of PCBs (Novak et al, 1988;Peeters et al, 2001). The Grasse River contains a 7.2-mile stretch of unremediated PCB-contaminated sediments originating from the ALCOA plant at the uppermost point in the AOC (http:// www.thegrasseriver.com/index.html, accessed September 5, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Test materials Reinhold-Dudok van Heel and Den Besten (1999) and Peeters et al (2001) provide an extended description of the area selected for this study. Sediments and soils were sampled in 1999 along two sites comprising gradients of aquatic to terrestrial locations: 1) shallow water, 2) shallow water with reeds, 3) an intertidal mud flat, 4) reed vegetation, and 5) a marsh forest.…”
Section: Methodsmentioning
confidence: 99%
“…Because of seasonal high river discharges, the area is flooded once or twice each year, having caused widespread contamination of the terrestrial as well as the aquatic environment. Previous studies indicated serious environmental risks in the aquatic environment (Den Besten et al, 1995;Peeters et al, 2001), but little or no information is available concerning the terrestrial environment. With the decrease of industrial and domestic contamination over the past decades (Admiraal et al, 1993), the overall quality of newly deposited sediments in the river Rhine has improved.…”
Section: Introductionmentioning
confidence: 99%